The potential of ARL4C and its-mediated genes in atherosclerosis and agent development - Liu, Dan; Wang, Jie; Zhang, Shuangshuang; Jiang, Hongfei; Wu, Yudong; Wang, Chao; Chen, Wujun (Frontiers in Pharmacology, 2025)
Foam cells are the risk factors for atherosclerosis. Recently, ARL4C, a member of the ADP-ribosylation factor family of GTP-binding proteins, was found to promote cholesterol efflux to decrease foam cell formation, suggesting that ARL4C may be a new promising target for the treatment of atherosclerosis. In fact, ARL4C regulated the expression of multiple atherosis-related genes, including ABCA1, ALDH1A3, ARF6, ENHO, FLNA, LRP6, OSBPL5, Snail2, and SOX2. Many agents, including ABCA1 agonists (CS-6253, IMM-H007, RG7273, and R3R-01), FLNA antagonist sumifilam, LRP6 inhibitor BI-905677 and agonist SZN-1326, and SOX2 inhibitor STEMVAC, were investigated in clinical trials. Targeting these genes could improve the success rate of drug development in clinical trials. Indeed, many agents could regulate ARL4C expression, including LXR/RXR agonists, Ac-LDL, sucrose, T9-t11-CLA, and miR-26. Downregulation of ARL4C with siRNA and anti-sense oligonucleotide (ASO), such as ASO-1316, is developing in preclinical research for the treatment of lung adenocarcinoma, liver cancer, and colorectal cancer. Thus, ARL4C and its regulated genes may be a potential target for drug development. Thus, we focus on the role of ARL4C and its-mediated genes in atherosclerosis and agent development, which provide insights for the identification, research, and drug development of novel targets.